Microbial Keratitis After Collagen Cross-linking Treatment - Banu Torun Acar; Ece Turan Vural; Elvin Halili; Suphi Acar (Türk Oftalmoloji Dergisi)
A 33-year-old woman presented with pain, redness, and diminution of vision that occurred 2 days after collagen cross-linking had been performed for keratoconus in the right eye. Culture results from the patient's contact lens and corneal scrapings were positive for Staphylococcus epidermidis. According to the results of antibiotic susceptibility testing, the patient was treated with hourly topical fortified vancomycin and exocin. Before collagen cross-linking, the best-corrected visual acuity (BCVA) was 4/10, the manifest refraction was -7.00 -1.755 3°. Four months after the procedure, the BCVA was 4/10, the manifest refraction was -5.50 -1.75 10°. Slit-lamp examination revealed a mild residual haze in the upper midperipheral cornea, and stromal opacities had disappeared. Collagen crosslinking is less invasive compared to other methods for treatment of keratoconus, but epithelial debridement and bandage contact lens wearing may lead to the development of bacterial keratitis. (Turk J Oph thal mol 2012; 42: 300-2)